Looking Good is Good Business: The Social Milieu of Fashion in Lagos, Nigeria (Global Journal of Human-Social Science, 2020)
Fashion in the city of Lagos, Nigeria is a complex interplay of culture, individual taste, social andor economic status. Lagosians' fashion does not toll the line of any particular social fashion or lifestyle theory as it is a contextual construct of the local with the foreign to project a lifestyle of indigenous culture amidst a 'modern' global outlook. Contemporary fashion in Lagos reflects years of continued cosmopolitanism, negotiating local culture with foreign adaptations. Appearance is key in daily social negotiations and relationship formation, while clothing functions as an implicit conduit of these transactions.